2015
DOI: 10.1590/1983-1447.2015.04.54289
|View full text |Cite
|
Sign up to set email alerts
|

Educational strategies to improve adherence to patient identification

Abstract: Teaching strategies based on staff awareness improved the professionals' adherence to checking patient ID wristbands. In addition, this result can contribute to strengthening the safety culture within the institution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 8 publications
0
11
0
13
Order By: Relevance
“…To achieve these goals, teamwork among professionals and managers is essential, since the uncritical use of scientific knowledge or partial implementation of protocols in health institutions, without articulation with professionals, results in unsuccessful safety and quality desired, and may incur risks to the patients' health and the credibility of the institution. 19…”
Section: Discussionmentioning
confidence: 99%
“…To achieve these goals, teamwork among professionals and managers is essential, since the uncritical use of scientific knowledge or partial implementation of protocols in health institutions, without articulation with professionals, results in unsuccessful safety and quality desired, and may incur risks to the patients' health and the credibility of the institution. 19…”
Section: Discussionmentioning
confidence: 99%
“…The permanent education of a public policy for the formation of quality human resources is promoted as an evidence-based method for the implementation of patient safety measures. [20][21] In a study carried out with the nursing team in a hospital public of Porto Alegre, in which educational actions took place as a conversation wheel on the theme of Goal 1, was raised by the participants: the non-existence of patients identified with the wristband; boards in bed with incorrect information; conflict between management and care professionals and that the compulsory use of the wristband in an external sector would increase the number of patients identified. [19][20] It is believed that the identification of the patient and the maintenance of the wristband are the responsibility of the entire multiprofessional team.…”
Section: Resultsmentioning
confidence: 99%
“…[20][21] In a study carried out with the nursing team in a hospital public of Porto Alegre, in which educational actions took place as a conversation wheel on the theme of Goal 1, was raised by the participants: the non-existence of patients identified with the wristband; boards in bed with incorrect information; conflict between management and care professionals and that the compulsory use of the wristband in an external sector would increase the number of patients identified. [19][20] It is believed that the identification of the patient and the maintenance of the wristband are the responsibility of the entire multiprofessional team. [4][5][6][7]15,19 However, in the medical records, there were no records about the wristband for other professional categories besides the Nursing.…”
Section: Resultsmentioning
confidence: 99%
“…Teaching health workers the concepts that pervade quality and patient safety helps them understand the importance of these concepts, follow procedure, and practice safe care, and it strengthens team commitment. The strategies must focus on education and awareness regarding best practices and consolidating patient safety (18) . In this study, we observed an inclination toward this direction.…”
Section: Discussionmentioning
confidence: 99%